Framework‐Porphyrin‐Derived Single‐Atom Bifunctional Oxygen Electrocatalysts and their Applications in Zn–Air Batteries. Issue 19 (25th March 2019) - Li, Bo‐Quan; Zhao, Chang‐Xin; Chen, Shuangming; Liu, Jia‐Ning; Chen, Xiao; Song, Li; Zhang, Qiang
Abstract: High‐performance bifunctional oxygen electrocatalysis constitutes the key technique for the widespread application of clean and sustainable energy through electrochemical devices such as rechargeable Zn–air batteries. Single‐atom electrocatalysts with maximum atom efficiency are highly considered as an alternative of the present noble‐metal‐based electrocatalysts. However, the fabrication of transition metal single‐atoms is very challenging, requiring extensive attempts of precursors with novel design principles. Herein, an all‐covalently constructed cobalt‐coordinated framework porphyrin with graphene hybridization is innovatively designed and prepared as the pyrolysis precursor to fabricate single‐atom Co–N x –C electrocatalysts. Excellent electrochemical performances are realized for both bifunctional oxygen electrocatalysis and rechargeable Zn–air batteries with regard to reduced overpotentials, improved kinetics, and prolonged cycling stability comparable with noble‐metal‐based electrocatalysts. Design principles from multiple scales are proposed and rationalized with detailed mechanism investigation. This work not only provides a novel precursor for the fabrication of high‐performance single‐atom electrocatalysts, but also inspires further attempts to develop advanced materials and emerging applications. Abstract : Cobalt‐coordinated framework porphyrin hybridized with graphene is employed as the pyrolysis precursor to fabricate single‐atom Co–N x –C electrocatalysts. Excellent ORR/OER bifunctional electrocatalytic performances are achieved with a small overpotential gap of 0.87 V, and corresponding Zn–air batteries afford higher power density, improved rate performance, and cycling stability for over 200 cycles beyond the noble‐metal‐based electrocatalysts.